Efficacy of Aqueous Extracts of Thevetia Peruviana Seed Kernels in Combination or Not with Other Botanical Substrates in the Control of Cocoa Mirids in Togo - Kondow, Moubarak; Nyamador, Seth Wolali; Ablede , Komlan Adigninou; Ametefe, Komivi Exonam; Kadanga, Pana (European Journal of Applied Sciences, 2022)
Mirids are the most damaging insect pests of cocoa plants in Togo. In order to contribute to a sustainable management of these mirids, different botanical extracts were tested on the pests in the laboratory and in the field on an organic cocoa plantation in the Akébou prefecture. Four (4) different extracts were tested in the laboratory including a pure extract of Thevetia peruviana kernels (TPK); two combinations of TPK and Ocimum gratissimum leaves (TPK-OG), TPK and Hyptis suaveolens leaves (TPK-HS) and a combination of TPK, Azadirachta indica and Nicotiana tabacum (TPK-AI-NT). All the extracts were dosed at 30 g/l. At the end of the laboratory tests, 2 of the extracts, namely TPK 30 g/l and TPK-AI-NT 30 g/l were retained for the field efficacy tests. The direct contact toxicity method and the classical tarpaulin method of infested cocoa trees were used respectively in the laboratory and in the field to evaluate the mortality of mirids. The tested extracts were compared to a reference bioinsecticide, NIMBEX. Tap water was used in the laboratory as a negative control. All data collected were analyzed using the IBM SPSS Statistics 20 software. Mirid mortality rates obtained in the laboratory ranged from 0% with tap water to 96.67 ± 5.77% with TPK 30 g/l. TPK-OG 30 g/l, TPK-HS 30 g/l and TPK-AI-NT 30 g/l extracts produced 63.33 ± 5.77%, 60% and 93.33 ± 5.77% mirid mortality, respectively, and NIMBEX produced 76.67 ± 5.77% mirid mortality. In the field, the efficiency was 80 ± 28.28% for TPK 30 g/l and 76.19 ± 13.47% with TPK-AI-NT 30 g/l while NIMBEX caused a mortality of 62.5 ± 17.68%. The application of these results will contribute to a sustainable management of cocoa mirids in Togo.